2006
DOI: 10.1111/j.1600-6143.2006.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Donor Kidney Pool: Utility of Renal Allografts Procured in a Setting of Uncontrolled Cardiac Death

Abstract: The chronic shortage of deceased kidney donors has led to increased utilization of donation after cardiac death (DCD) kidneys, the majority of which are procured in a controlled setting. The objective of this study is to evaluate transplantation outcomes from uncontrolled DCD (uDCD) donors and evaluate their utility as a source of donor kidneys. Concerted efforts should be focused on procurement of uDCD donors, which can provide another source of quality deceased donor kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 21 publications
2
71
0
3
Order By: Relevance
“…Over the last decade as experience with DCD transplantation has grown, many single center studies have reported equivalent long-term graft survival and equivalent rates of primary non-function (PNF) between recipients of DCD kidneys and SCD kidneys (10,(12)(13)(14)(15)(16)(17)(18). Further, several retrospective analyses of the United Network for Organ Sharing (UNOS) database, including reports by Rudich et al and more recently Doshi and Hunsicker, have compared short and long term outcomes among recipients of DBD and DCD kidneys, and have demonstrated that DCD kidneys have equivalent patient and graft survival rates at 5 years compared to DBD (SCD and ECD) kidneys (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade as experience with DCD transplantation has grown, many single center studies have reported equivalent long-term graft survival and equivalent rates of primary non-function (PNF) between recipients of DCD kidneys and SCD kidneys (10,(12)(13)(14)(15)(16)(17)(18). Further, several retrospective analyses of the United Network for Organ Sharing (UNOS) database, including reports by Rudich et al and more recently Doshi and Hunsicker, have compared short and long term outcomes among recipients of DBD and DCD kidneys, and have demonstrated that DCD kidneys have equivalent patient and graft survival rates at 5 years compared to DBD (SCD and ECD) kidneys (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated, however, that effective use of these potential donors would add greatly to the number of organ donors [10]. This contrasts with the situation in renal transplantation in which organs from uncontrolled DCD have been used by some centres with outcomes that compare well with those from controlled DCD donors [11]. Following renal transplantation, a period of 'delayed graft function' is acceptable because it is possible to support the patient with dialysis whilst the transplanted organ recovers from the ischaemic injury; an equivalent delay in initial function of a transplanted liver is fatal without urgent re-transplantation.…”
Section: Donation After Circulatory Death (Dcd)mentioning
confidence: 58%
“…Fifty-five percent of patients needed at least one session of hemodialysis (DGF) postoperatively [60] . Use of DCD whether controlled or uncontrolled is associated with high PNF and DGF but the long term outcome is satisfactory (Table 2) [7,19,61] . However, some reports showed no significant difference between DCD and DBD.…”
Section: Dgf and Primary Non Functionmentioning
confidence: 99%
“…Gagandeep et al [7] 2006 Sanchez-Fructuoso et al [55] 2000 (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998) Sanchez-Fructuoso et al [65] 2004 (1990-1998) Cooper et al [70] 2004 ( Akoh JA. Kidney donation after cardiac death increased, DBD decreased by 20% in the three countries with a predominant controlled DCD activity, while DBD had increased in the majority of European countries.…”
Section: Series Type Number Patient Survival (%) Graft Survival (%) Dmentioning
confidence: 99%
See 1 more Smart Citation